HUBUNGAN PERILAKU PETANI DENGAN PRODUKTIVITAS JERUK SIAM DI KECAMATAN BUKIT KERMAN KABUPATEN KERINCI - Prasojo, prasojo; Lubis, Arsyad; Aprollita, Aprollita (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
This study aims to know: (1) knowing the behavior of farmers in the cultivation of Siamese in Bukit Kerman District Kerinci Regency. (2) knowing the productivity of Siamese farming in Bukit Kerman District Kerinci Regency. (3) find out the relationship between the behavior of farmers and the productivity of siam orange farming in Bukit Kerman District Kerinci Regency. Sampling is done by saturated sampling method. The results of the analysis obtained the value of X2 hit > X2 tab which means that there is a relationship between behavior and productivity of Siamese oranges in Bukit Kerman District Kerinci Regency, with a degree of 0.412 which means that the relationship between behavior and productivity is relatively strong because the value lies between 0.354 - 0.707. Obtained a correlation degree of 0.582, which means the closeness of the relationship between behavior and productivity of Siamese in Bukit Kerman Subdistrict, Kerinci Regency is classified as moderate. Furthermore, the thit> ttab value means that there is a significant relationship between behavior and productivity of Siamese in the Bukit Kerman Subdistrict of Kerinci District in real terms. Keywords: Behavior, Productivity, Siam Orange Cultivation